Solve for x (complex solution)
x=\frac{i\sqrt{99-20\sqrt{5}}}{2}+5\sqrt{5}+\frac{1}{2}\approx 11.680339887+3.683701958i
x=-\frac{i\sqrt{99-20\sqrt{5}}}{2}+5\sqrt{5}+\frac{1}{2}\approx 11.680339887-3.683701958i
Graph
Share
Copied to clipboard
25\left(\sqrt{5}\right)^{2}-10\sqrt{5}x+x^{2}+25=x
Use binomial theorem \left(a-b\right)^{2}=a^{2}-2ab+b^{2} to expand \left(5\sqrt{5}-x\right)^{2}.
25\times 5-10\sqrt{5}x+x^{2}+25=x
The square of \sqrt{5} is 5.
125-10\sqrt{5}x+x^{2}+25=x
Multiply 25 and 5 to get 125.
150-10\sqrt{5}x+x^{2}=x
Add 125 and 25 to get 150.
150-10\sqrt{5}x+x^{2}-x=0
Subtract x from both sides.
150+\left(-10\sqrt{5}-1\right)x+x^{2}=0
Combine all terms containing x.
x^{2}+\left(-10\sqrt{5}-1\right)x+150=0
All equations of the form ax^{2}+bx+c=0 can be solved using the quadratic formula: \frac{-b±\sqrt{b^{2}-4ac}}{2a}. The quadratic formula gives two solutions, one when ± is addition and one when it is subtraction.
x=\frac{-\left(-10\sqrt{5}-1\right)±\sqrt{\left(-10\sqrt{5}-1\right)^{2}-4\times 150}}{2}
This equation is in standard form: ax^{2}+bx+c=0. Substitute 1 for a, -10\sqrt{5}-1 for b, and 150 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
x=\frac{-\left(-10\sqrt{5}-1\right)±\sqrt{20\sqrt{5}+501-4\times 150}}{2}
Square -10\sqrt{5}-1.
x=\frac{-\left(-10\sqrt{5}-1\right)±\sqrt{20\sqrt{5}+501-600}}{2}
Multiply -4 times 150.
x=\frac{-\left(-10\sqrt{5}-1\right)±\sqrt{20\sqrt{5}-99}}{2}
Add 501+20\sqrt{5} to -600.
x=\frac{-\left(-10\sqrt{5}-1\right)±i\sqrt{99-20\sqrt{5}}}{2}
Take the square root of -99+20\sqrt{5}.
x=\frac{10\sqrt{5}+1±i\sqrt{99-20\sqrt{5}}}{2}
The opposite of -10\sqrt{5}-1 is 10\sqrt{5}+1.
x=\frac{10\sqrt{5}+1+i\sqrt{99-20\sqrt{5}}}{2}
Now solve the equation x=\frac{10\sqrt{5}+1±i\sqrt{99-20\sqrt{5}}}{2} when ± is plus. Add 10\sqrt{5}+1 to i\sqrt{99-20\sqrt{5}}.
x=\frac{i\sqrt{99-20\sqrt{5}}}{2}+5\sqrt{5}+\frac{1}{2}
Divide 10\sqrt{5}+1+i\sqrt{99-20\sqrt{5}} by 2.
x=\frac{-i\sqrt{99-20\sqrt{5}}+10\sqrt{5}+1}{2}
Now solve the equation x=\frac{10\sqrt{5}+1±i\sqrt{99-20\sqrt{5}}}{2} when ± is minus. Subtract i\sqrt{99-20\sqrt{5}} from 10\sqrt{5}+1.
x=-\frac{i\sqrt{99-20\sqrt{5}}}{2}+5\sqrt{5}+\frac{1}{2}
Divide 10\sqrt{5}+1-i\sqrt{99-20\sqrt{5}} by 2.
x=\frac{i\sqrt{99-20\sqrt{5}}}{2}+5\sqrt{5}+\frac{1}{2} x=-\frac{i\sqrt{99-20\sqrt{5}}}{2}+5\sqrt{5}+\frac{1}{2}
The equation is now solved.
25\left(\sqrt{5}\right)^{2}-10\sqrt{5}x+x^{2}+25=x
Use binomial theorem \left(a-b\right)^{2}=a^{2}-2ab+b^{2} to expand \left(5\sqrt{5}-x\right)^{2}.
25\times 5-10\sqrt{5}x+x^{2}+25=x
The square of \sqrt{5} is 5.
125-10\sqrt{5}x+x^{2}+25=x
Multiply 25 and 5 to get 125.
150-10\sqrt{5}x+x^{2}=x
Add 125 and 25 to get 150.
150-10\sqrt{5}x+x^{2}-x=0
Subtract x from both sides.
-10\sqrt{5}x+x^{2}-x=-150
Subtract 150 from both sides. Anything subtracted from zero gives its negation.
\left(-10\sqrt{5}-1\right)x+x^{2}=-150
Combine all terms containing x.
x^{2}+\left(-10\sqrt{5}-1\right)x=-150
Quadratic equations such as this one can be solved by completing the square. In order to complete the square, the equation must first be in the form x^{2}+bx=c.
x^{2}+\left(-10\sqrt{5}-1\right)x+\left(-5\sqrt{5}-\frac{1}{2}\right)^{2}=-150+\left(-5\sqrt{5}-\frac{1}{2}\right)^{2}
Divide -10\sqrt{5}-1, the coefficient of the x term, by 2 to get -5\sqrt{5}-\frac{1}{2}. Then add the square of -5\sqrt{5}-\frac{1}{2} to both sides of the equation. This step makes the left hand side of the equation a perfect square.
x^{2}+\left(-10\sqrt{5}-1\right)x+5\sqrt{5}+\frac{501}{4}=-150+5\sqrt{5}+\frac{501}{4}
Square -5\sqrt{5}-\frac{1}{2}.
x^{2}+\left(-10\sqrt{5}-1\right)x+5\sqrt{5}+\frac{501}{4}=5\sqrt{5}-\frac{99}{4}
Add -150 to \frac{501}{4}+5\sqrt{5}.
\left(x-5\sqrt{5}-\frac{1}{2}\right)^{2}=5\sqrt{5}-\frac{99}{4}
Factor x^{2}+\left(-10\sqrt{5}-1\right)x+5\sqrt{5}+\frac{501}{4}. In general, when x^{2}+bx+c is a perfect square, it can always be factored as \left(x+\frac{b}{2}\right)^{2}.
\sqrt{\left(x-5\sqrt{5}-\frac{1}{2}\right)^{2}}=\sqrt{5\sqrt{5}-\frac{99}{4}}
Take the square root of both sides of the equation.
x-5\sqrt{5}-\frac{1}{2}=\frac{i\sqrt{99-20\sqrt{5}}}{2} x-5\sqrt{5}-\frac{1}{2}=-\frac{i\sqrt{99-20\sqrt{5}}}{2}
Simplify.
x=\frac{i\sqrt{99-20\sqrt{5}}}{2}+5\sqrt{5}+\frac{1}{2} x=-\frac{i\sqrt{99-20\sqrt{5}}}{2}+5\sqrt{5}+\frac{1}{2}
Subtract -5\sqrt{5}-\frac{1}{2} from both sides of the equation.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}